THE EFFECT OF PRACTICUM LEARNING METHODS ON STUDENTS SCIENCE PROCESS ACTIVITIES AND SKILLS ECOSYSTEM MATERIAL IN CLASS X IPA MAN 1 LANGSA - Dwi Mutia Sari Elfrida Ekariana S Pandia (Jurnal Biologi Sains dan Kependidikan, 2022)
ABSTRACTThe practicum method is a method that makes students directly involved themselves in doing and following a process of observing, analyzing, proving and drawing conclusions about an object. So that science process skills in learning can be taught and trained through experimental activities. The purpose of this study was to determine the effect of practicum learning methods on students' science process activities and skills on ecosystem material in class X IPA MAN 1 Langsa. The sample used is class X IPA 2 with a total of 24 students as the experimental class and class X IPA 3 with a total of 25 students in the control class. This study uses an experimental design that is True Experimental Design. The data collection technique used in this study is observation sheets and documentation and data analysis using the T test. The results of this study conclude that there is an effect of practical learning methods on students' science process activities and skills on ecosystem material. in class X IPA MAN 1 Langsa significantly with activity values of 2,438 1,677 and science process skills of 4,174 1,677.Keywords: learning activities, science process skills, practicum method